SEISMIC DATA ANALYSIS OF FRACTURED META-SEDIMENT IN EAST COAST PENINSULAR MALAYSIA: ANALOGUE TO FRACTURED BASEMENT IN MALAY BASIN - Rosely, Liyana (Universiti Teknologi PETRONAS, 2015)
In the oil and gas industry, basins containing fractured basement have garnered much interest due to the fractures’ potential as a hydrocarbon reservoir (Sircar, 2004) through its secondary porosity. However, since these basements are typically made of meta-sediments or igneous rock located at a deeper depth, it is difficult to analyze the fracture network based on seismic images, due to poor resolution (attenuation of higher frequency, and lack of sedimentary layers with contrasting acoustic impedance). Thus, imaging, locating and interpreting the fracture network within the basement proves to be a challenge, and results in a higher risk of inaccurate drilling decisions to be made. Having surface outcrops which can serve as a good analogue to the subsurface provides an opportunity for in-depth studies at a fraction of the cost for well-based studies. Hence, this study aims to image the basement fractures in Anding field better through seismic processing, and correlate them with the fractures found on onshore outcrops at the coast of Terengganu, peninsular Malaysia.